The Impacts of Conversational Implicature to Characterization of Miss Peregrine in "Miss Peregrine's Home for Peculiar Children" Movie - Chairiza Shaula Akhna; Lina Purwaning Hartanti (ELS Journal on Interdisciplinary Studies in Humanities, 2026)
Conversational implicature is a pragmatic phenomenon in which speakers convey implicit meanings that can only be interpreted through context, shared knowledge, and situational understanding. In movie dialogue, conversational implicature functions as a linguistic device for character development. This study aims to examine the impact of conversational implicature on Miss Peregrine’s characterization in “Miss Peregrine’s Home for Peculiar Children” movie. Using a qualitative method, this study analyses Miss Peregrine’s utterances containing conversational implicature as the research data. The analysis based on Grice’s (1945) theory of conversational implicature and Zhang’s (2025) theory of characterization, which encompasses the aspects of identity, attitude and evaluation, social relations, and power. The findings indicate that conversational implicature plays a significant role in portraying Miss Peregrine as a wise, protective, strategic, nurturing, and authoritative character. Miss Peregrine’s regulates circumstances, upholds her authority, maintains the group’s emotional stability, and builds social relationship with the peculiar children by using ambiguity, indirect utterances, and information restriction. The results reveal that the aspect of power is the most dominant in Miss Peregrine’s Peregrine characterization. Therefore, this study highlights that conversational implicature not only functions as a strategy for conveying implicit meanings but also acts as a linguistic mechanism that contributes to character development in movie dialogue.